PSYCHOANALYSIS IN INITIAL TEACHER TRAINING FOR ELEMENTARY EDUCATION: A BRIEF LITERATURE REVIEW - Machado dos Santos, Adelcio; Marcia Twardowski, Rita; Alves dos Santos Caetano, Audete; Martins Leffer, Danielle; André Escher, Alisson (Revista Gênero e Interdisciplinaridade, 2026)
This article analyzes the contributions of Psychoanalysis to initial teacher education in basic education through a qualitative literature review. It is based on the assumption that teacher education, traditionally focused on technical and pedagogical aspects, lacks approaches that address the subjective dimension of the educational process. In this context, Psychoanalysis, founded by Sigmund Freud, provides relevant theoretical support for understanding the subject in its complexity, considering the influence of the unconscious, affects, and interpersonal relationships on learning. The study discusses key concepts such as transference, desire, and the subject of the unconscious, drawing on classical authors such as Jacques Lacan and Donald Winnicott, articulating them with the educational context. The findings indicate that incorporating Psychoanalysis into teacher education promotes a more reflective, ethical, and sensitive pedagogical practice, contributing to the understanding of phenomena such as learning difficulties, indiscipline, and psychological distress. Furthermore, it highlights the importance of listening and the teacher’s subjective involvement in their practice. However, the study also points out challenges, such as the predominance of technicist curricula and the risk of superficial appropriations of psychoanalytic concepts. It concludes that integrating Psychoanalysis into teacher education can significantly enrich the educational process when carried out critically and theoretically grounded.